Amylenes Do Not Lead to Bacterial Mutagenicity in Contrast to Structurally Related Epoxides. (6th January 2014) - Westphal, Götz A.; Tüshaus, Carolin; Monsé, Christian; Rosenkranz, Nina; Brüning, Thomas; Bünger, Jürgen
Abstract : Amylenes are unsaturated hydrocarbons (C5 H10 ), such as 1-pentene, 2-pentene, 2-methyl-but-1-en (3-methyl-1-butene), 2-methyl-but-2-en (isopentene), and 3-methyl-but-1-en. We investigated bacterial mutagenicity of 1-pentene, 2-pentene, and 3-methyl-but-1-en in the Ames test. 2-Pentene was investigated as racemate and as pure diastereomers. We included the methyltransferase deficient Salmonella Typhimurium strain YG7108 and the application of a gas-tight preincubation to reduce the risk of false negative results. 1, 2-Epoxypentane which may arise from 1-pentene was used as positive control. None of the investigated amylenes showed mutagenic effects, whereas 1, 2-epoxypentane was mutagenic exceeding 100  μ g per plate. An exceptional high reverse mutation in the negative control plates in the experiments with 1, 2-epoxypentane was obviously caused by evaporation into the incubator which was shown by placing the control plates in a separate apparatus. No differences were seen upon use of YG7108 and its parent strain TA1535. In conclusion, 1, 2-epoxypentane is most probably not a substrate of the deleted bacterial methyltransferases. The comparison of the bacterial mutagenicity of the investigated amylenes and 1, 2-epoxipentane suggests that epoxidation of amylenes in the S9-mix does not proceed effectively or is counterbalanced by detoxifying reactions. The assessment of mutagenic effects of short chained aliphatic epoxides can be underestimated due to the evaporation of these compounds.